Genetics and thermal biology of littorinid snails of the genera Afrolittorina, Echinolittorina and Littoraria (Gastropoda: Littorinidae) from temperate, subtropical and tropical regions - Matumba, Tshifhiwa Given (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2013)
With the anticipated effects of climate change due to global warming, there is concern over how animals, especially ectotherms, will respond to or tolerate extreme and fluctuating environmental temperature stress. Littorinid snails are intertidal ectotherms that live high on the shore where they experience both extreme and variable conditions of temperature and desiccation stress, and are believed to live close to their tolerance limits. This study investigated the thermal biology of littorinid snails of the genera Afrolittorina, Echinolittorina and Littoraria from temperate, subtropical and tropical regions in South Africa and Brunei Darussalam using thermal tolerance, heart function, and proteome approaches. The effects of conditions, such as rate of change in temperature, acclimation, heat shock, season and starvation were also tested. In addition, the evolutionary relationships and genetic diversity between and within the South African Afrolittorina spp. were investigated using mitochondrial and nuclear markers. Genetic results confirmed that these are two distinct species, with the brown to black A. knysnaensis predominant in the cool-temperate region of South Africa and the pale blue-grey A. africana in the subtropical region. There was low genetic variation and differentiation within each species, suggesting high gene flow among populations as a result of the effects of ocean currents on the dispersal of their planktotrophic larvae. Tests using exposure to high temperatures revealed differences in the thermal tolerances, heart performance and protein profiles of species from different latitudes, regions and zones on the shore. Thermal tolerance conformed to expectations, with clear, statistically significant trends from high tolerance in subtropical species to lower tolerance in temperate species. However, for Afrolittorina spp., there were no significant differences in the thermal tolerances of conspecifics from different regions, though there was a significant difference in thermal tolerance between juveniles and adults. Overall, adults of all species showed higher thermal tolerances than juveniles. Although lethal temperatures for these species were higher in summer than winter, laboratory acclimation had no effect on heat coma temperatures. All species showed some regulation of heart rate, with a degree of independence of heart rate from temperature across mid-range temperatures. The tropical species showed quick induction and good regulation of heart rate followed by the subtropical and temperate species, which displayed mixed responses including regulation, partial regulation and lack of regulation. Overall, tropical Echinolittorina spp. showed good regulation, while the subtropical E. natalensis and Littoraria glabrata exhibited a mixture of partial regulation and regulation. The subtropical/temperate Afrolittorina spp. showed high individual variability, some animals exhibiting regulation, while others did not. These effects seem to be largely phylogenetically determined as there were no differences in the heart rate responses of Afrolittorina spp. from different regions. The temperatures at which heart rate became independent of temperature (thermoneutral zone) were within the range experienced under natural conditions. In addition, there were differences in Arrhenius breakpoint and endpoint temperatures, showing a trend from higher in tropical animals to lower for temperate animals. Conditions such as acclimation, heat shock and starvation had little or no effect on heart performance. However, a slow increase in temperature induced good regulation of heart rate with noticeable shifts of breakpoints and endpoints for Afrolittorina spp. Lastly, there were differences in the proteome responses between and within Afrolittorina spp. as a function of species, size and treatment. Although both large and small A. knysnaensis had a greater number of protein spots in their proteome than A. africana (though the difference was not significant), the later showed significantly higher differential expression of certain proteins following heat stress. In addition, juveniles of both species displayed greater numbers of protein spots in their proteome than adults. The results indicate a difference in the physiological and biochemical responses (i.e. adaptations) of these snails to temperature, and this seems to relate to differences in biogeography, phylogeny, species identity and ecology. The ability to regulate heart rate is phylogenetically determined, while thresholds and lethal limits correspond to biogeography and species ecology. The proteome seems to correspond to species ecology. The results also indicate that these littorinids can tolerate high temperature stress and in this respect they are well suited to life in the intertidal zones or habitats where temperature and other stresses or conditions are extreme and can change abruptly. However, the limited ability of these snails to acclimate to different temperatures suggests that they are already living close to their tolerance limits with small safety margins or narrow thermal windows and so may be vulnerable to small rises in substratum temperature and/or solar radiation.
Keywords: Littorinidae -- South Africa; Littorinidae -- Brunei; Littorinidae -- Adaptation -- South Africa; Littorinidae -- Adaptation -- Brunei; Littorinidae -- Effect of temperature on -- South Africa; Littorinidae -- Effect of temperature on -- Brunei; Littorinidae -- Physiology; Snails -- South Africa; Snails -- Brunei; Gastropoda -- South Africa; Gastropoda -- Brunei; Intertidal animals -- South Africa; Intertidal animals -- Brunei